2017
DOI: 10.5194/aab-60-95-2017
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone (P4), luteinizing hormone (LH) levels and ovarian activity in postpartum Santa Inês ewes subject to a male effect

Abstract: Abstract. This study aimed to establish P4 and luteinizing hormone (LH) levels and ovarian activity as approaches to monitor the cyclicity of ewes under postpartum anestrus after the male effect approach. Santa Inês females (n = 66) were evenly distributed into experimental groups where they were brought into contact with an intact male during the postpartum period of 35 to 40 days (T1) and 55 and 60 days postpartum (T2). Ewes were isolated from males for 30 days before the onset of the experiment. Estrus even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
(29 reference statements)
2
8
0
Order By: Relevance
“…These results showed that WK has a comparatively long breeding season when compared with other northern hemisphere sheep breeds (Bartlewski et al, 1999a;Dell'Aquila et al, 1988;Gómez-Brunet et al, 2008). The results from our anestrous P4 levels were also similar with anestrous P4 levels from other sheep breed (Ferreira-Silva et al, 2017;Sasa, Rodrigues, Nonaka, Balieiro, & Coelho, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…These results showed that WK has a comparatively long breeding season when compared with other northern hemisphere sheep breeds (Bartlewski et al, 1999a;Dell'Aquila et al, 1988;Gómez-Brunet et al, 2008). The results from our anestrous P4 levels were also similar with anestrous P4 levels from other sheep breed (Ferreira-Silva et al, 2017;Sasa, Rodrigues, Nonaka, Balieiro, & Coelho, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…For example, the exposure of the male to the female with temporary weaning for 24 h improved the reproductive performance in ewes under postpartum anestrous ( 54 ). Also, the male effect promotes pre-ovulatory LH peaks up to 80 h after physical contact ( 55 ).…”
Section: Discussionmentioning
confidence: 99%
“…(2005) reported that the ewes may be synchronized using either GnRH‐PGF2α program or two injections of PGF2α 10 days apart. Ovarian activity of postpartum (35 to 60 days after lambing) ewes was resumed by the ram effect (Ferreira‐Silva et al., 2017). So, the male effect is efficient to induce ovarian activity and increase progesterone concentration in the control ewes.…”
Section: Discussionmentioning
confidence: 99%